A NEW SIMPLIFIED APPROACH TO FIND THE EQUIVALENT RESISTANCE OF ANY COMPLEX EQUAL RESISTIVE NETWORK - Aneja, Karan; Kumar, Vipin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
As we are familiar with the star-delta transformation to determining the equivalent resistance [4] between any two terminals of a complex network and to find the overall current of a closed circuit, but sometimes circuit become too complex such that it consumes a lots of time while solving the network to find the equivalent resistance between two known terminals. So, here we have developed a new simplified approach for the solution to find the equivalent resistance between the desired terminals for equal resistance network and to find the overall current in a closed circuit.